2022
DOI: 10.7759/cureus.28453
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Study of the Plaque Removal Efficacy of a Novel Manual Toothbrush With Micro-Pulse Bristles on Fixed Orthodontic Patients

Abstract: Background Fixed orthodontic appliances on tooth surfaces, such as brackets and bands, complicate oral hygiene and increase plaque accumulation, contributing to gingivitis, periodontitis, and tooth decay. While manual toothbrushes are an essential part of oral hygiene, there is little clinical evidence to demonstrate how effective manual toothbrushes with novel designs are at removing plaque from orthodontic patients. This study aims to evaluate three types of manual toothbrushes (Pulsar, convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This effect occurs when participants in a study modify their behavior or performance simply because they are aware of being observed or receiving special attention. In an RCT evaluating a novel manual toothbrush design for orthodontic patients, the methodology necessitated that patients brush in front of the investigator[ 15 ]. This could have led to the Hawthorne effect as the performance of patients in home brushing may not be same as that in brushing in front of the dentist.…”
Section: Special Biasmentioning
confidence: 99%
“…This effect occurs when participants in a study modify their behavior or performance simply because they are aware of being observed or receiving special attention. In an RCT evaluating a novel manual toothbrush design for orthodontic patients, the methodology necessitated that patients brush in front of the investigator[ 15 ]. This could have led to the Hawthorne effect as the performance of patients in home brushing may not be same as that in brushing in front of the dentist.…”
Section: Special Biasmentioning
confidence: 99%